2007
DOI: 10.1007/s00464-007-9503-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open liver resection for hepatocellular carcinoma in patients with histologically proven cirrhosis: short- and middle-term results

Abstract: This study shows that LH for HCC in properly selected cirrhotic patients results in fewer early postoperative complications and a shorter hospital stay than the traditional OH. The 2-year survival rate was the same for LH and OH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
180
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(196 citation statements)
references
References 32 publications
8
180
1
6
Order By: Relevance
“…A margem cirúrgica foi adequada na maioria dos relatos: com uma média de mais de 1,0 cm em quase todas as séries publicadas e com poucos casos de margens cirúrgicas comprometidas 3,4,5 Embora promissores, a análise destes resultados deve levar em consideração o fato de que as séries com ressecção VL envolvem pacientes altamente selecionados, com doença metastática limitada, enquanto as séries com ressecções laparotômicas de MHCCR incluem pacientes com doença mais extensa e procedimentos mais complexos. Por essa razão, um maior número de estudos é necessário para que se possam delimitar com maior precisão os resultados das ressecções VL para MHCCR.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…A margem cirúrgica foi adequada na maioria dos relatos: com uma média de mais de 1,0 cm em quase todas as séries publicadas e com poucos casos de margens cirúrgicas comprometidas 3,4,5 Embora promissores, a análise destes resultados deve levar em consideração o fato de que as séries com ressecção VL envolvem pacientes altamente selecionados, com doença metastática limitada, enquanto as séries com ressecções laparotômicas de MHCCR incluem pacientes com doença mais extensa e procedimentos mais complexos. Por essa razão, um maior número de estudos é necessário para que se possam delimitar com maior precisão os resultados das ressecções VL para MHCCR.…”
Section: Resultsunclassified
“…Benefícios específicos do acesso VL são a preservação da parede abdominal e sua circulação colateral venosa, diminuindo assim o regime de hipertensão portal no pós-operatório, menor necessidade de reposição volêmica e melhor reabsorção da ascite pela preservação peritoneal 7 . Alguns grupos têm demonstrado benefício das ressecções laparoscópicas para pequenos CHC em cirróticos, com diminuição da morbidade, em especial na ocorrência de ascite pós-operatória 3,8,11,26 . Dois estudos caso-controle compararam os resultados de ressecções hepáticas VL e abertas em pacientes cirróticos.…”
Section: Tumores Primáriosunclassified
See 1 more Smart Citation
“…2,[11][12][13] Numerous studies have demonstrated that oncologic outcomes such as resection margins and disease-free survival were comparable with open resection. 2 Furthermore, laparoscopic LR is associated with improved perioperative and short-term outcomes such as decreased hospital stay and decreased blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…2 Furthermore, laparoscopic LR is associated with improved perioperative and short-term outcomes such as decreased hospital stay and decreased blood loss. 2 HALS LR has been advocated by some authors as an alternative to pure laparoscopy, 6,13 especially for "technically difficult" resections. 6 Hand control of the liver may theoretically allow for a better margin of resection, decrease blood loss by direct compression, and improve surgical exposure.…”
Section: Discussionmentioning
confidence: 99%